Рецензія на монографію - Kulbabska, Olena (Посвіт, 2021)
In the monograph the comprehensive analysis of the communicative specificity of the elitist linguistic personality (ELP) in the scientific discourse focusing on a wide range of its presentation originality. It clarifies the dimensions of the elitist linguistic personality objectifications in various aspects (psychological, social, philosophical, cultural ones), explains the ELP concept essence, substantiates the criteria of its isolation basing on the typical features inherent for the high speech culture mediums , which is respectively tested on the famous personalities’ media, epistolary, artistic, diary discourses, and the famous Ukrainian linguists’ communicative explications material.
Keywords: communicative strategy, communicative tactics, elitist linguistic personality, linguistic personality structural organization, linguo-individualization, scientific-linguistic discourse, verbal